Proto-fuse project: Methods to boost [spatial] creativity - Hakak, Alireza Mahdizadeh; Bhattacharya, Joydeep (A+BE | Architecture and the Built Environment, 2018)
This chapter, via two experiments, focuses on proving the hypothesis with empirical evidences. Two separate experiments were conducted under the title: The Proto-fuse project. In each of these experiments the following two concepts and their correlation with creativity have been addressed: 1- Conceptual blending 2- Tolerance of ambiguity The experiments firstly aim to identify the relationship between conceptual blending and navigating UVEs and secondly aim to identify the importance of tolerances of ambiguity in the discipline of architecture and engineering. The empirical evidences are published in the fourth journal article: “The Proto-Fuse project: methods to boost creativity for architects”, International Journal of Design Creativity and Innovation, Taylor & Francis publisher, pp. 1-16.